Challenges Faced by Teachers in Teaching English at Basic Level - Saud, Mohan Singh (Education and Development, 2020)
Teaching English as a foreign language can be a challenging job in non-English speaking countries like Nepal, particularly when English is taught as a subject. In consideration of English as an international language in Nepal, this study explored the challenges faced by English language teachers in teaching English at basic level pubic school education in Dhangadhi Sub-Metropolitan City of Kailali district of Nepal. Using a phenomenological design under qualitative research, the study included four English language teachers selected through non-random, purposive sampling technique. Semi-structured interviews were used to collect information from the participants, and then the data were analysed and discussed thematically in line with the research questions. As the results revealed, the key challenge concerned large class sizes, particularly when the students came from poor economic family backgrounds, those who also had a poor English language base with low vocabulary achievement. Managing larger classes, recruiting more teachers having English language proficiency and managing infrastructures along with extending class hour can be its implications. Exposing students to English forms the base.